Harding’s Syndrome – Clinical Case Report and Literature Review - Jesus, Jeniffer Domingues; Soares, Raquel; Matias, Maria João; Geraldes, Rafael; Brandão, Eva; Silva, Renata; Chibante, João (Revista Sociedade Portuguesa de Oftalmologia, 2020)
INTRODUCTION Leber's Hereditary Optic Neuropathy (LHON) is a maternally inherited disease that manifests as painless bilateral visual loss, usually in early adulthood. Patients with LHON associated with Multiple Sclerosis were mostly female and the association of both pathologies is termed as "Harding's disease". CASE REPORT A 21-year-old woman presented with a typical episode of optic neuritis (ON) in the right eye, which led to Multiple Sclerosis (MS) diagnosis after imagiological and analytical investigation. The episodes of optic neuritis were repeated, with progressive severe visual impairment and the lack of recovery with the treatment for acute attacks, which warned the possibility of LHON. The diagnose was supported by genetic tests by detecting a mutation of the mtDNA 11778 base pair. The patient started oral Idebenone 900mg/day and remained stable for 12 months, with progressive RE visual recovery. Genetic tests for her mother were also applied and the same mutation was identified, which supports the diagnosis of LHON even in her mother, although she always remained without visual symptoms. DISCUSSION Due to the presentation and optic disc findings, LHON is frequently misdiagnosed as ON in the context of MS. However, continuous vision loss in patients with MS during the treatment should raise suspicion for an alternative diagnosis. CONCLUSIONS LHON associated with MS is suggested to be a distinct entity with challenging diagnose and more severe involvement of optic nerve. Our case highlights the importance of genetic tests in individuals who present recurrent ON, with reduced visual recovery during the treatment, even if there is a positive study for MS and no identified family history for LHON. Keywords: Leber's Hereditary Optic Neuropathy, Multiple Sclerosis, Harding's disease, Neuroinflammation, Neurodegeneration